An Evolutionary Way to Standardize the Internet of Things - Shen, Subin; Carugi, Marco (Journal of ICT Standardization, 2014)
The current situation of technology separation among the different application domains of the Internet of Things (IoT) results in a market separation per application domain. This issue hinders the technical innovation and investments in the IoT business. In order to solve the issue, it is necessary to standardize common technologies of the IoT across the different application domains. This paper argues that a key direction of the future standardization of the IoT, in addition to standardizing specific technologies, is building over a standardized new architecture reference model for the IoT. Based on the analysis of existing key activities concerning the standardization of OSI, NGN and IoT from a functional architecture perspective, it suggests that the IoT standardization work be progressed in an evolutionary way in order to enable the integration of existing technologies, and focus on the interactions among functional entities or deployable components of the IoT to impose minimum constraints on future technical innovations. Topics discussed in the paper include characteristic capabilities of the IoT, ways of integrating the cloud computing technologies in the IoT perspective, and challenges faced by the IoT standardization work.